Internalization of Religious Moderation Values: Active Tolerance and Social Harmony in Education in Indonesia - Mufi, Akhmad Munir; Elhady, Aminullah; Mursalim (Universitas Islam Indonesia, 2023)
Amidst the ongoing violence in the name of religion, it is important to instill the values of religious moderation in society. Schools, as important agents in community education, require specific strategies to cultivate these values. This research aims to describe the concept of interfaith moderation and the stages of its internalization in schools to foster tolerance. In this study, the researcher employs a qualitative descriptive research design. Data collection and processing are conducted through literature review and qualitative analysis. Data is gathered from books, scholarly journal articles, and other relevant sources, and then analyzed. This study argues that religious moderation is a balanced attitude in the application of religious teachings. It is important to internalize this attitude in students at school to foster tolerance towards individuals with different beliefs, particularly due to the continued existence of violence carried out in the name of religion. There are three stages of instilling the values of religious moderation: value transformation, value transaction, and value transinternalization. In schools, these stages are carried out through formal and hidden curricula.